Chlorhexidine cytotoxicity on oral Behaviors: Last 20 Years systematic review - Luca Fiorillo; Cesare D'Amico; Vini Mehta; Marco Cicciù; Gabriele Cervino (Oral Oncology Reports)
Objectives: Modern dentistry has made available a series of cariostatic pharmacological products with beneficial positive effects on oral health. One of the most commonly prescribed and used drugs is chlorhexidine. This active ingredient, derived from chlorine in gel and mouthwash formulations, is widely used thanks to its antiseptic properties even in the post-surgical phases and takes place in many prophylactic protocols. This review aims to highlight the cytotoxic effects of this active ingredient on oral tissue cells. Methods: The review considered all the studies related to the topic (208). After skimming the results and isolating only recent studies (20 years) written in English and accessible, it was possible to define the number of articles to be included. in the review. Results: Only 14 articles were included in the systematic review. All these in vitro studies evaluate the cytotoxicity and antimicrobial effect of Chlorhexidine alone or in combination with other compounds. All manuscripts according that cytotoxic effect in vitro is present at a concentration major than 0.001%. Conclusion: In conclusion, the cytotoxicity of chlorhexidine on oral cells and tissues is a complex issue that requires further investigation. While its efficacy in reducing bacterial populations and preventing oral infections is well established, the long-term impact of chlorhexidine on oral health should be considered in the context of its potential cytotoxicity. Practitioners should use chlorhexidine judiciously and be aware of the patient's specific needs and risk factors when deciding on its use in oral health procedures.